Evaluation of Simultaneous Fitting Method for \(β\)-Decay Half-Lives and \(β\)-Delayed Multi Neutron Emission Probabilities Developed for the Briken Experiment - Phong, Vi Ho; Nishimura, Shunji; Khiem, Le Hong (Communications in Physics, 2018)
This paper presents a Monte-Carlo code to simulate the time sequences of the \(β\)-decay following implantation of a continuous radioactive ion beam in to a segmented silicon detector. We extended our simulation to the \(β\)-delayed neutron process. Ananalis is procedure, which has been developed to obtain simultaneously the \(β\)-decay half-life and the \(β\)-delayed multi-neutron emission probability, was verified by the simulation data